2021
DOI: 10.3390/md19020059
|View full text |Cite
|
Sign up to set email alerts
|

Seaweed-Based Compounds and Products for Sustainable Protection against Plant Pathogens

Abstract: Sustainable agricultural practices increasingly demand novel, environmentally friendly compounds which induce plant immunity against pathogens. Stimulating plant immunity using seaweed extracts is a highly viable strategy, as these formulations contain many bio-elicitors (phyco-elicitors) which can significantly boost natural plant immunity. Certain bioactive elicitors present in a multitude of extracts of seaweeds (both commercially available and bench-scale laboratory formulations) activate pathogen-associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 204 publications
(341 reference statements)
2
37
0
Order By: Relevance
“…Several macroscopic algae are used in the production of biostimulants, although in recent times, particular attention has been placed on the species Ascophyllum nodosum, Ecklonia maxima and Kappaphycus alvarezii, as well as the genera Gracilaria spp. [106].…”
Section: Seaweed Extractsmentioning
confidence: 99%
“…Several macroscopic algae are used in the production of biostimulants, although in recent times, particular attention has been placed on the species Ascophyllum nodosum, Ecklonia maxima and Kappaphycus alvarezii, as well as the genera Gracilaria spp. [106].…”
Section: Seaweed Extractsmentioning
confidence: 99%
“…For example, Ghaderiardakani et al [8] found that extracts from Ulva species contained a range of hormones that had both inhibitory and stimulatory effects on plant growth and development. It is well recognised that extracts from various major groups of macroalgae, including the two species used in the current study, contain a wide range of biologically active compounds including plant hormones such as cytokinins [9], laminarins, alginates, phenolics, ulvans, and carrageenans [6,10,11]. However, the mechanisms that underly the effect of seaweed extracts on plants remains unclear.…”
Section: Introductionmentioning
confidence: 98%
“…Seaweed extracts are compositionally diverse and complex in nature [3]. Recent reviews [6,7] confirm the great diversity in extracts derived from macroalgae and the wide variety of physiological responses to specific components of the extracts. For example, Ghaderiardakani et al [8] found that extracts from Ulva species contained a range of hormones that had both inhibitory and stimulatory effects on plant growth and development.…”
Section: Introductionmentioning
confidence: 99%
“…Ulvan is able to reduce the disease severity in different host-pathogen biosystems [ 7 ], by stimulation of specific enzymatic activities, salicylic acid production, and increase in phenolic compounds [ 15 , 26 ], as well as being involved in the jasmonic acid signaling pathway in leaves of Arabidopsis thaliana (L.) [ 7 ]. Ulvan induced an activation of the plant immune system through the expression of the defense-related marker gene PR10 up to 15 days in Medicago young plants [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ulvan bioactivity is, thus, multi-faceted, as it prepares the plant to better respond to stress (priming effect), it acts on plant genes involved in the immune response, as well as on enzymatic activities in the biosynthetic pathways of stress-protective metabolites. On the basis of the induced resistance against pathogenic fungi, recently, the ulvan seaweed extract has been selected as new sustainable and highly viable strategy for the stimulation of plant immunity [ 26 ].…”
Section: Discussionmentioning
confidence: 99%